Needle nephroscope combined with ureteroscope via a single standard percutaneous nephrolithotomy channel for the treatment of complex non-obstructing renal stones - Yi, Xinyu; Li, Jin (Frontiers in Surgery, 2025)
ObjectiveTo compare the safety and efficacy of four different surgical approaches for the treatment of complex non-hydronephrotic renal stones.MethodsA total of 88 patients with complex non-hydronephrotic renal stones, who underwent surgical treatment at Xiangtan Central Hospital from January 2022 to December 2023, were included in this study. The patients were divided into two groups based on their CT values. Group 1 (CT ≥ 1,000) included 22 patients who underwent puncture-assisted single standard percutaneous nephrolithotomy (PCNL) with a laser for stone fragmentation and retrieval (experimental group), and 12 patients who underwent multi-standard percutaneous nephrolithotomy (control group). Group 2 (CT < 1,000) included 21 patients who underwent puncture-assisted single standard PCNL combined with ureteroscopic laser lithotripsy (experimental group), and 33 patients who underwent transurethral ureteroscopic laser lithotripsy (control group). The surgical variables including intraoperative blood loss, operative time, hospital stay, stone clearance rate, and postoperative complications were recorded. Statistical analysis was performed using chi-square test or Fisher's exact test for categorical data, and t-test for continuous data.ResultsThe two groups were comparable in terms of age, sex, BMI, hypertension, coronary heart disease, diabetes, and preoperative white blood cell count (P > 0.01). In both CT ≥ 1,000 and CT < 1,000 groups, the experimental group had significantly less intraoperative blood loss, shorter operative time, and shorter hospital stay compared to the control group (P < 0.01). In the CT ≥ 1,000 control group, the stone clearance rate was higher, and two cases of postoperative bleeding (considered arteriovenous fistula) were managed with interventional embolization. In the CT < 1,000 control group, the stone clearance rate was lower, and three cases of postoperative fever (with a maximum temperature of 39.5°C) required an extended antibiotic course for 7 days before discharge.ConclusionFor complex non-hydronephrotic renal stones, a CT value ≥ 1,000 should be treated with single standard PCNL using a puncture-assisted method; a CT value < 1,000 is better treated with a combination of puncture-assisted single standard PCNL and ureteroscopic laser lithotripsy, with higher safety and efficacy.